What Factors Influence Non-Adherence to the Smoking Cessation Program? - Koçak, Nagihan Durmuş (Turk Thorac J, 2019)
OBJECTIVES: To improve our knowledge and understand how to deal with non-adherence to the support programs and to determine the rate and possible factors related to non-adherence in subjects who attended our smoking cessation clinic. MATERIALS AND METHODS: This was a case-control study that included 550 subjects who applied to our smoking cessation clinic between June 1, 2011 and December 31, 2011. After a 1-year follow-up period, subjects were divided into two groups: adherent (controls) and non-adherent (cases). Sociodemographic and clinical parameters and smoking habits were evaluated. A p value <0.05 was considered significant. RESULTS: Of the 550 subjects, the number of cases (non-adherent) was 135 (24.6%), and the number of controls (adherent) was 415 (75.4%). Age to begin smoking was significantly young in subjects with non-adherence to the program (p=0.026). The rate of receiving pharmacotherapy was significantly high in subjects with adherence (p<0.0001). No difference was found between the groups according to varenicline, bupropion, nicotine gum, or combined therapy use, whereas nicotine patch use alone significantly increased the rate of non-adherence (p=0.022). Multivariable logistic regression analysis showed that the age to begin smoking (p=0.045, odds ratio (OR): 1.05, 95% confidence interval (CI): 0.86–0.99) and pharmacotherapy (p<0.0001, OR: 5.00, 95% CI: 2.80–8.94) were independent variables that affected adherence to the program. CONCLUSION: Care should be taken in the follow-up period when providing no pharmacotherapy and with subjects who started smoking at a young age.